Law against Drugs: National and International Cooperation - Verma, Pushp Lata (SCHOOL SCIENCE, 2018)
The problem of drug trafficking continues to take a significant toll on valuable human lives across the globe. With our vulnerable geographical position between the two major drug producing regions—the Golden Triangle and Golden Crescent, there are a number of challenges before the law enforcement agencies in India. The Government of India is well aware about the menace and our enforcement agencies in coordination with agencies of neighbouring countries are making all efforts to contain the problem.The Narcotics Control Bureau (NCB) is the nodal agency for matters relating to drug law enforcement. It acts as the national coordinator for intelligence and enforcement coordination with international agencies. In addition, several educators acknowledged that drug abuse among students are important hurdle to the achievement of educational goals. Substance utilisation has also demonstrated to be connected with a number of negative education related consequences, including school drop-out. This has an impact on the area of education to make sure inclusive and equitable quality education for everyone and to achieve the new global 2030 Agenda for Sustainable Development